L-type amino acid transporter 1 is associated with chemoresistance in breast cancer via the promotion of amino acid metabolism - Miku Sato; Narumi Harada-Shoji; Takafumi Toyohara; Tomoyoshi Soga; Masatoshi Itoh; Minoru Miyashita; Hiroshi Tada; Masakazu Amari; Naohiko Anzai; Shozo Furumoto; Takaaki Abe; Takashi Suzuki; et al. (Scientific Reports, 2021)
Abstract 18F-FDG PET/CT has been used as an indicator of chemotherapy effects, but cancer cells can remain even when no FDG uptake is detected, indicating the importance of exploring other metabolomic pathways. Therefore, we explored the amino acid metabolism, including L-type amino acid transporter-1 (LAT1), in breast cancer tissues and clarified the role of LAT1 in therapeutic resistance and clinical outcomes of patients. We evaluated LAT1 expression before and after neoadjuvant chemotherapy and examined the correlation of glucose uptake using FDG-PET with the pathological response of patients. It revealed that LAT1 levels correlated with proliferation after chemotherapy, and amino acid and glucose metabolism were closely correlated. In addition, LAT1 was considered to be involved in treatment resistance and sensitivity only in luminal type breast cancer. Results of in vitro analyses revealed that LAT1 promoted amino acid uptake, which contributed to energy production by supplying amino acids to the TCA cycle. However, in MCF-7 cells treated with chemotherapeutic agents, oncometabolites and branched-chain amino acids also played a pivotal role in energy production and drug resistance, despite decreased glucose metabolism. In conclusion, LAT1 was involved in drug resistance and could be a novel therapeutic target against chemotherapy resistance in luminal type breast cancer.